Plasma Cytokine Profiles in Long-Term Strenuous Exercise. (28th April 2016) - Nielsen, Hilde G.; Øktedalen, Olav; Opstad, Per-Kristian; Lyberg, Torstein
Abstract : The open window theory indicates altered immunity 3 to 72 hours after exercise. The J-curve describes the risk of illness in response to exercise. The aim of this study was to examine the secretion of proinflammatory and anti-inflammatory cytokines before and after long-term strenuous exercise. Fourteen marathon and 16 half-marathon runners and 10 military cadets participating in a military ranger-training course were recruited to this study. Within-subject design was used measuring levels of plasma cytokines before, during, and after exercise. Plasma cytokines were measured using Luminex multiplex technology and ELISA. Comparing pre/post plasma levels both the marathon- and the half-marathon runners showed heavily increased levels of IL-6, IL-10, and IL-8 (P < 0.001 ). LPS stimulation among the half-marathon runners decreased the postrace levels of IL-6, IL-1b, and TNF α by 45%, 24%, and 43%, respectively (P < 0.01 ). During the ranger training course the spontaneous and LPS-stimulated levels of IL-6, IL-8, IL-10, IL-1b, and TNF α changed in a similar fashion as in the half-marathon runners although the fluctuations were smaller. Our study supports the open window and the J-curve theory; the immune system is more activated and the subjects are more threatened to infectious pathogens after intensive physical activity and in the period after exercise.